Robert Holschuh Simmons. Demagogues, Power, and Friendship in Classical Athens. Leaders as Friends in Aristophanes, Euripides, and Xenophon. London: Bloomsbury, 2023. 177 pp., ISBN 978-1-350-21448-4 - Mariana Franco San Román (Synthesis (La Plata))
Reseña de  Demagogues, Power, and Friendship in Classical Athens. Leaders as Friends in Aristophanes, Euripides, and Xenophon de R. Holschuh Simmons por M. Franco San Román.